A green and high throughput method for salt determination in crude oil using digital image-based colorimetry in a portable device. (1st April 2021) - Holkem, Alice P.; Voss, Mônica; Schlesner, Sandra K.; Helfer, Gilson A.; Costa, Adilson B.; Barin, Juliano S.; Müller, Edson I.; Mello, Paola A.
Graphical abstract: Highlights: Chloride determination by digital images-based colorimetric analysis. A green extraction method for salt determination in crude oil. A simple, high throughput and low-cost method for chloride using PhotoMetrix UVC. Greenness of the method calculated with the Analytical GREEnness (AGREE) calculator. Abstract: A digital image-based (DIB) method using colorimetry via a portable device is proposed for salt determination in crude oil. Chloride was extracted to an aqueous phase, followed by colorimetric quantification using digital images. A USB camera was attached to a homemade 3D-printed chamber with controlled light intensity. The images were converted into red, green, and blue (RGB) histograms, and a partial least squares regression (PLS) model was constructed using the free PhotoMetrix UVC app. The experimental parameters were optimized, as the ratio between silver nitrate and the potassium chromate, the lighting, the volume of solution in the measurement chamber, the focal distance, and the pH effect. A miniaturized extraction method was developed for sample preparation, and the main parameters were evaluated: sample mass, time, temperature, solvent, or the use of a demulsifier and its amount. The PLS regression model was evaluated in terms of the coefficient of determination (R 2 ), the root mean squared error of calibration (RMSEC), the root mean squared error of cross validation (RMSECV) and the root mean squared error of prediction (RMSEP). The detection limit was 69 mg L −1 (0.034 mg g −1 using 10 g of sample). No differences were observed (p < 0.05) when comparing the results from the DIB method with the reference values. The extraction method's simplicity combined with the digital image-based colorimetric analysis allowed an easy-to-use and environmentally friendly method. Other important advantages include low cost, the possibility to be portable, and high throughput in comparison to standard methods.